Identification and pathogenicity of Alternaria and Fusarium species associated with bagged apple black spot disease in Shaanxi, China - Ding, Dandan; Shao, Yating; Zhao, Jirong; Lin, Jinshui; Zhang, Xiangqian; Wang, Xiukang; Xu, Xiangming; Xu, Chengnan (Frontiers in Microbiology, 2024)
Apple is an economically important fruit crop in northern Shaanxi Province in China. In recent years, a new type of apple black spot disease, "bagged apple black spot disease", has occurred in the main apple production area of Yan'an City, Shaanxi Province, during the apple ripening season. It seriously affects the appearance quality and commercial value of apples. In this study, 120 isolates recovered from symptomatic apples were identified based on morphological characteristics, pathogenicity, and multilocus sequence analyses of the internal transcribed spacer of ribosomal DNA (rDNA-ITS), translation elongation factor 1-α (EF1-α), RNA polymerase II subunit B (RPB2), endopolygalacturonase (endo-PG), and anonymous region OPA1-3. Alternaria alternata was the most abundant species (64%), followed by Fusarium acuminatum (36%). Pathogenicity assays were conducted by inoculating them individually and together on detached apples (Venus Golden and Fuji varieties). The results showed that the two fungal species could infect apples individually and together. Co-infection enhanced the disease severity. F. acuminatum led to increased severity and speed of disease development compared to A. alternata. This is the first report of Fusarium and Alternaria coinfection causing apple black spot disease worldwide, and the first report of F. acuminatum affecting apples. The optimal growth of A. alternata occurred at 25-30℃ and pH 7; the optimal growth of F. acuminatum occurred at 25℃ and pH 7. The results of this study can provide a theoretical basis for exploring the occurrence and epidemiology of apple black spot disease and strategies for its control.